Design of an Improved MPPT Control of DFIG Wind Turbine under Unbalanced Grid Voltage using a Flux Sliding Mode Observer - Youssef Majdoub; Ahmed Abbou; Mohamed Akherraz; Rachid El Akhrif (Institute of Advanced Engineering and Science, 2017)
This study presents a control scheme of the electronic interface of a grid connected Variable Speed Wind Energy Generation System (VS-WEGS) based on a Doubly Fed Induction Generator (DFIG). The efficiency of the wind energy is represented to according to the control strategy applied. Thus, in the case of unbalanced grid voltage, the negative sequence voltage causes additional strong oscillation at twice the grid frequency in the stator instantaneous active and reactive powers. The objective of this work is to present an enhanced MPPT controller uses backstepping approach implemented in both and reference frames rotating to keep a safe operation of DFIG during unbalanced grid voltage associated with regulating rotor flux, in order to estimate rotor flux, a nonlinear observer based on sliding mode is proposed in this work. Note that the conventional controllers (PI, PI-R …) are not provided satisfactory performance during unbalanced voltage dips. The validation of results has been performed through simulation studies on a 4 kW DFIG using Matlab/Simulink®.